Spatiotemporal Changes and Effects of Urban Commercial Bank Expansion in the Yangtze River Economic Belt, China - Li Yingyi; Zhao Jinli (Redai dili)
Urban commercial banks are a primary force that supports local economies and alleviates the financing challenges faced by small- and medium-sized enterprises. However, these banks have experienced substantial changes in their overall strengths and diversified management capabilities over the past two decades of development. Previous studies have indicated that numerous issues persist amid these ongoing changes and expansions. It is therefore crucial to investigate the expansion pathways and associated effects to ensure the sustainable development of urban commercial banks in China. Therefore, we used unbalanced panel data from 46 urban commercial banks in the Yangtze River Economic Belt from 1996 to 2023 with spatial network analysis and econometric modeling to delineate the spatiotemporal changes related to both endogenous and exogenous expansions. We also examined how remote expansion influenced the efficiency levels of urban commercial banks. The endogenous expansion of urban commercial banks exhibited notable fluctuations in its intensity and geographical reach. Under the combined influence of mechanisms that favor optimal selection and neighboring connections, inter-city, inter-provincial, and regional administrative barriers were dismantled. Consequently, some expansion-path heterogeneity existed across different regions and scales. Nevertheless, these expansion networks were consistently concentrated within the Yangtze River Economic Belt, which is characterized by concentrated activity in its eastern segments, and exhibited sporadic distributions beyond this belt. Notably, radial expansions within provinces were predominant. The intensity of exogenous expansion was relatively limited. Rural banks acted as the primary focus of their expansion efforts. Urban commercial banks tend to favor out-of-province expansions, particularly among eastern urban commercial banks (e.g., Chouzhou and Mintai banks). The expanded numbers and geographic reaches of urban commercial banks significantly enhanced their efficiency levels at the 1% significance level. Scale and time heterogeneity analyses indicate that small-sized urban commercial banks have a greater propensity to increase their efficiencies. There was a pronounced contribution to the asset scale of these banks during the early stages of urban commercial banking development. The robust expansion capacity during this initial phase facilitated more effective improvements in market share and capital adequacy ratios, thereby consolidating foundational strength. However, owing to data limitations, this study did not conduct a more comprehensive analysis of the effects. Future research should conduct more detailed comparative studies of the expansion and contraction dynamics within urban business networks by utilizing richer datasets and broader methodological approaches.